2011
DOI: 10.1182/blood-2010-07-294272
|View full text |Cite
|
Sign up to set email alerts
|

IRF8 and IRF3 cooperatively regulate rapid interferon-β induction in human blood monocytes

Abstract: Robust and rapid induction of interferon-␤ (IFN-␤) in monocytes after pathogenic stimulation is a hallmark of innate immune responses. Here, we reveal the molecular mechanism underlying this key property that is exclusive to human blood monocytes. We found that IFN-␤ was produced rapidly in primary human monocytes as a result of cooperation between the myeloid-specific transcription factor IRF8 and the ubiquitous transcription factor IRF3. Knockdown of IRF8 in monocytes abrogated IFN-␤ transcription, whereas r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
65
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 41 publications
3
65
0
Order By: Relevance
“…5D) confirmed that the Ifnb1 gene promoter was constitutively bound by IRF8 and that PU.1 association with it was largely IRF8 dependent. Binding of IRF8 and PU.1 to the IFNb promoter in human and mouse monocytes was previously mapped to promoter sites resembling PWM1 (a composite ETS/IRF site that differs from PWM1 because of a 4-nt spacer between the 59-GGAA-39 ETS consensus and the 59-GAAA-39 IRF consensus) and PWM4 (Li et al 2011) and is fully consistent with our ChIP-seq data. Moreover, constitutive IRF8/PU.1 binding was shown to be required for IRF3 recruitment, thus explaining reduced IFNb induction in cells depleted of IRF8 (Li et al 2011).…”
Section: Basal and Inducible Gene Expression Programs Regulated By Irf8supporting
confidence: 88%
“…5D) confirmed that the Ifnb1 gene promoter was constitutively bound by IRF8 and that PU.1 association with it was largely IRF8 dependent. Binding of IRF8 and PU.1 to the IFNb promoter in human and mouse monocytes was previously mapped to promoter sites resembling PWM1 (a composite ETS/IRF site that differs from PWM1 because of a 4-nt spacer between the 59-GGAA-39 ETS consensus and the 59-GAAA-39 IRF consensus) and PWM4 (Li et al 2011) and is fully consistent with our ChIP-seq data. Moreover, constitutive IRF8/PU.1 binding was shown to be required for IRF3 recruitment, thus explaining reduced IFNb induction in cells depleted of IRF8 (Li et al 2011).…”
Section: Basal and Inducible Gene Expression Programs Regulated By Irf8supporting
confidence: 88%
“…First, the spleen and head kidney of zebrafish were collected for total RNA extraction at 4,8,12,20,32, or 48 h postinfection with SVCV. mRNAs were made using the polyATtract mRNA isolation system (Promega) and used for construction of a 1 3 10 6 CFU BacterioMatch II two-hybrid system library, according to the manufacturer's instructions (Agilent).…”
Section: B1h Assaysmentioning
confidence: 99%
“…In addition to IRF3/7, accumulating evidence suggests that IRF1, IRF5, and IRF8 trigger IFN responses in cell-specific fashions (5)(6)(7)(8). IRF1 is the founder member of the IRF family and initially was identified as a positive regulator directly binding to type I IFN gene promoters (9).…”
mentioning
confidence: 99%
“…IRF8 directs the IFN response, together with IRF3/7, in DCs (18) and with IRF3 in human blood monocytes (19). IRF3, IRF5, and IRF7 coordinately act in myeloid DCs downstream of mitochondrial antiviral signaling protein signaling (20).…”
mentioning
confidence: 99%